2018
DOI: 10.20884/1.mib.2018.35.1.592
|View full text |Cite
|
Sign up to set email alerts
|

Keanekaragaman Ikan di Sungai Luk Ulo Kabupaten Kebumen

Abstract: Freshwater fish is one of the biodiversity that build river ecosystem structure. Many human activities are carried out in the river as well as in the surrounding areas, such as removal of household waste, excessive fish exploitation and land use activities. This might changes river characteristics and lead to population and biodiversity decline.This research aim to 1) analyzethe diversity and species composition of fishin Luk Ulo River of Kebumen Regency,and 2) analyze the interaction among environmental facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 0 publications
0
11
0
9
Order By: Relevance
“…The results of field observations and identification in the laboratory found seven types of fish species divided into seven families along the Cikaniki river (Table 1), the number found was less than the research results Ridho et al (2003), who saw nine types of fish families in the Cikaniki river.The decrease in the number of fish can be caused by habitat destruction, including those related to an increase in population, industrial activities, land use and management changes, economic policies in development, and high poverty levels (Wahyuni & Zakaria, 2018). The study results as a whole, the composition of the fish species found in Cikaniki River at station 3 was more diverse than other stations.…”
Section: Findings and Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…The results of field observations and identification in the laboratory found seven types of fish species divided into seven families along the Cikaniki river (Table 1), the number found was less than the research results Ridho et al (2003), who saw nine types of fish families in the Cikaniki river.The decrease in the number of fish can be caused by habitat destruction, including those related to an increase in population, industrial activities, land use and management changes, economic policies in development, and high poverty levels (Wahyuni & Zakaria, 2018). The study results as a whole, the composition of the fish species found in Cikaniki River at station 3 was more diverse than other stations.…”
Section: Findings and Discussionmentioning
confidence: 78%
“…The data obtained is the result of direct field measurements (temperature, pH) and laboratory measurements (BOD, COD, DO) can be seen in Table 2. The composition and distribution of fish are strongly influenced by changes in physics, chemistry, and biology (Wahyuni & Zakaria, 2018). Measurement of environmental factors aims to see the effect of water conditions on aquatic resource communities.…”
Section: Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kemelimpahan dapat menggambarkan keadaan serta jenis ikan air tawar yang mendominasi suatu tempat. Keragaman dan kelimpahan ikan juga dipengaruhi oleh faktor fisik dan kimia lingkungan seperti: suhu, kadar keasaman air atau pH, tingkat kekeruhan atau kecerahan air, kecepatan arus air, dan kadar oksigen yang terkandung di dalam perairan (Wahyuni & Zakaria, 2018) khususnya perairan rawa.…”
Section: Metodeunclassified
“…Tinggi-rendahnya keanekaragaman dan kelimpahan ikan pada suatu kawasan juga dapat dijadikan sebagai indikator tingkat kesehatan perairan diarea tersebut (Wahyuni, 2018).…”
Section: Pendahuluanunclassified